Breast Imaging Reporting and Data System (BI RADS) - why we don’t use it correctly in the region? - Prvulović Bunović, Nataša; Mastilović, Milica; Stankov, Maja; Nikolin, Borislava (Archive of Oncology, 2024)
Breast Imaging Reporting and Data System (BI RADS) is used for the standardization of radiological reports in breast imaging, created by the American college of radiology (ACR). Standardized reports allow breast lesion characterization, malignancy risk assessment, and facilitate communication between doctors. The system is made for everyday clinical practice with the aim to improve the quality of diagnostics and anticipate comparison of results with colleagues from another health institutions, while in Serbia to assist in communication with colleagues from the region. BI RADS system is composed of a lexicon recommendations for structured radiological reporting and further management. Most of the health institutions in Serbia and surrounding countries use it, but in everyday clinical practice the system is not correctly implemented in all institutions. During daily imaging procedures we see radiological reports coming from different institutions in the region. Some of them clearly show that the system is misunderstood and not implemented in a correct way. Our aim is to evaluate the use of BI RADS system in everyday clinical practice in Serbia and region, to explain why it is not used correctly, to point out the most common mistakes made, with the desire to make the system work adequately.